Ecuador : The Faces of Informality (Las Caras de La Informalidad) - World Bank (Washington, DC, 2013)
Informality hampers economic performance at both macro and micro levels. High degree of informality and low economic growth tend to go hand-in-hand, although evidence shows that the relationship likely comes from common determinants of both. Informality in Ecuador remains high compared to other countries. This study offers a novel look at informality in Ecuador by directly asking firm owners and workers about their views and behavior. The analysis of the causes and costs of informality for firms in Ecuador in this study is based on data from a 2011 enterprise survey commissioned specifically for this study and complemented by focus groups and in-depth interviews. The survey captures the aspects of the regulatory framework which are most problematic for compliance, and the specific reasons for non-compliance. The study focuses on micro and small firms in the urban areas of Ecuador. The sectors of activity, geographic locations, and sizes of firms covered by this study were agreed upon with the Government during the initial consultations on the report. The study finds that many micro and small firms in Ecuador have limited growth potential, due to low entrepreneurial ability and lack of access to and poor quality of credit.